2019
DOI: 10.1159/000497464
|View full text |Cite
|
Sign up to set email alerts
|

Progression after Immunotherapy for Fibrolamellar Carcinoma

Abstract: Background: Fibrolamellar carcinoma (FLC) is a rare malignancy of the liver that differs from typical hepatocellular carcinoma (HCC) in several aspects such as the absence of underlying liver disease and occurrence in younger patients. Even though the survival rates in FLC are slightly better than in typical HCC, the prognosis of metastatic FLC remains deleterious. Several reports suggest that systemic chemotherapy regimens can successfully be used to halt disease progression in FLC, while targeted tumor thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
0
14
0
3
Order By: Relevance
“…76,78 Casereports on the use of ICIs are limited and response varies from progression to CR. 79 Notably CR was achieved in a patient with PD-L1 expression of 10%. 78 Therefore, further research is required to define the role of ICIs in the treatment of FLHCC (Table 2).…”
Section: Patients With Fibrolamellar and Mixed Hepato-cholangiocellulmentioning
confidence: 97%
“…76,78 Casereports on the use of ICIs are limited and response varies from progression to CR. 79 Notably CR was achieved in a patient with PD-L1 expression of 10%. 78 Therefore, further research is required to define the role of ICIs in the treatment of FLHCC (Table 2).…”
Section: Patients With Fibrolamellar and Mixed Hepato-cholangiocellulmentioning
confidence: 97%
“…However, one might argue that these two patients might be bad candidates or did not have good criteria to receive more courses to show activity. The ineffectiveness and the early progression were also noticed in the study that used immunotherapy in the three cases of metastatic FLC [ 32 ].…”
Section: Discussionmentioning
confidence: 98%
“…One study reported 41% of MSH2 mutations with next-generation sequencing of FLC tumor tissue. In this study, three cases of metastatic FLC progressed after 2–3 months of starting PD-L1 antibodies, one treated with pembrolizumab, and the other two received nivolumab, although the progression was below 20% [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…У обоих развилось прогрессирование заболевания через 2 и 3 мес. соответственно [73]. Однако в другом случае отмечен полный ответ после двух месяцев терапии ниволумабом, который продолжался и после 11 мес.…”
Section: лекарственная терапия флкunclassified